2018
DOI: 10.1016/j.ajpath.2017.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Expression of Hydrogen Sulfide–Generating Enzymes Down-Regulates 15-Hydroxyprostaglandin Dehydrogenase in Chorion during Term and Preterm Labor

Abstract: Chorionic NAD-dependent 15-hydroxyprostaglandin dehydrogenase (PGDH) plays a pivotal role in controlling the amount of prostaglandins in the uterus and has been implicated in the process of labor. Prior studies identified hydrogen sulfide-generating enzymes cystathionine-β-synthetase (CBS) and cystathionine-γ-lyase (CSE) in fetal membranes. We investigated whether hydrogen sulfide is involved in the regulation of PGDH expression in the chorion during labor. The chorionic tissues were obtained from pregnant wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…CBS is more abundant in rats [303]. CBS and CSE expression is lower in TL membranes compared with TNL cesarean controls [304]. Since sulfide attenuates oxidative stress and inhibits prostaglandin synthesis, CBS expression might reduce inflammation and delay membrane rupture [305].…”
Section: Rupture Of Membranesmentioning
confidence: 99%
“…CBS is more abundant in rats [303]. CBS and CSE expression is lower in TL membranes compared with TNL cesarean controls [304]. Since sulfide attenuates oxidative stress and inhibits prostaglandin synthesis, CBS expression might reduce inflammation and delay membrane rupture [305].…”
Section: Rupture Of Membranesmentioning
confidence: 99%
“…Our previous study demonstrated that human placenta samples express H 2 S synthetase, CSE and CBS, and deficiency of CSE and CBS in the placenta is associated with preeclampsia ( 32 ). Previous studies have also reported that deficiency in H 2 S synthetase is associated with other pregnancy complications, including premature labor ( 33 ) and fetal growth restriction ( 34 ). Thus, H 2 S may participate in the pathogenesis of GDM by regulating activation of the NLPR3 inflammasome in placentas.…”
Section: Introductionmentioning
confidence: 99%
“… 25 , 26 Our previous study found that the expression levels of the H 2 S-generating enzymes CBS and CSE and the production of H 2 S are decreased with the onset of labour and preterm labour in human chorionic tissues and the myometrium. 27 , 28 Furthermore, our studies have demonstrated that H 2 S produced by CSE and CBS contributes to uterine quiescence during pregnancy, 28 which suggests that H 2 S is involved in the initiation of labour. However, the mechanism by which H 2 S contributes to uterine quiescence and the regulation of labour remains largely unknown.…”
Section: Introductionmentioning
confidence: 77%